The Influence of The Soft Skill Competence of STIP Cadets on International Seafarer Competition - Nazilul Hamidi; Ronald Simanjuntak; Ulung Tri Sagitha Setya; Yozar Firdaus Amrullah (Dinasti Publisher, 2024)
Effectively implemented maritime education and training (MET) is essential to improve the competence of Indonesian seafarers in the international arena. This research examines the influence of STIP cadets' soft skills competencies. The two methods used were surveys and interviews with respondents from foreign shipping companies and maritime agents. These companies expect cadets who graduate from STIP as officers to be not only experts in hard skills competencies, but also capable of soft skills, which include the ability to manage crew, adaptability, problem solving and communication skills, as well as the ability to make presentations and give good explanations in English as communication skills. The research method used was a quantitative approach. It was found that adaptability 4,583 and teamwork 4.419 played a big role compared to problem solving 4.360 and communication 4.272. Changes in the adaptation of habits and daily activities in English in the STIP campus environment to support MET improvement are expected to increase the absorption of STIP cadets in international shipping companies.